The impact of cognitive processes in the areas of organizational changeApplied Study in the Directorate General of Training and Development / Ministry of Electricity - الجبوري علياء جاسم (Journal of Economics and Administrative Sciences, 2011)
Centric study on the interest of the Directorate General of Training and Development / Ministry of Electricity to consolidate the concept of process and enhancement of knowledge in the areas of organizational change، it reached a sample of the study (44) people who are highly heads of departments، technicians and administrators in different sections of the Directorate and by using the correlation coefficient (Spearman) & coefficient of simple regression been tested correlations between variables and the impact of the study، as has been reached to integrate the role of cognitive processes with the areas of organizational change and relationships that were significant at the level of overall dimensions and subsidiary organs.